Novel CARMIL2 loss-of-function variants are associated with pediatric inflammatory bowel disease - Luca Bosa (Nature Portfolio, 2021)
Abstract CARMIL2 is required for CD28-mediated co-stimulation of NF-κB signaling in T cells and its deficiency has been associated with primary immunodeficiency and, recently, very early onset inflammatory bowel disease (IBD). Here we describe the identification of novel biallelic CARMIL2 variants in three patients presenting with pediatric-onset IBD and in one with autoimmune polyendocrine syndrome (APS). None manifested overt clinical signs of immunodeficiency before their diagnosis. The first patient presented with very early onset IBD. His brother was found homozygous for the same CARMIL2 null variant and diagnosed with APS. Two other IBD patients were found homozygous for a nonsense and a missense CARMIL2 variant, respectively, and they both experienced a complicated postoperative course marked by severe infections. Immunostaining of bowel biopsies showed reduced CARMIL2 expression in all the three patients with IBD. Western blot and immunofluorescence of transfected cells revealed an altered expression pattern of the missense variant. Our work expands the genotypic and phenotypic spectrum of CARMIL2 deficiency, which can present with either IBD or APS, aside from classic immunodeficiency manifestations. CARMIL2 should be included in the diagnostic work-up of patients with suspected monogenic IBD.